Statistic surveys of innovation among enterprises in processing and manufactoring sectors in Vietnam - Luat, Ho Ngoc; Dung, Pham The (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Statistic surveys of innovation by enterprises are activities of statistic collection of data conducted in science and technology (S&T) sectors of Vietnam. They are quite a new type of activities in practice of Vietnam. Actually, Vietnam is implementing the survey methodology among enterprises on basis of OECD guidelines for a pilot survey among enterprises in processing and manufacturing sectors of Vietnam. On basis of methodology of statistic surveys by OECD, an option of statistic surveys of innovation was designed and implemented for investigation of about 8,000 enterprises in processing and manufacturing sectors over 44 provinces and center-controlled cities. The outcomes of the survey confirm are: (i) the methodology of statistic surveys of innovation can be applied for enterprises in Vietnam; (ii) the statistic indexes of innovation are set up scientifically and have values for practical use; and (iii) the statistic survey of innovation is feasible for the context of Vietnam. Some outcomes of the pilot survey, certain initial evaluations on basis of synthesis and assessment of the survey outcomes were noted to draw the global status of innovation activities of enterprises in processing and manufacturing sectors of Vietnam during 2014-2016 period. On this basis, some recommendations are proposed to promote and enhance effectiveness of innovation activities among enterprises in Vietnam. Code: 18100801 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">